PERANAN KREDIT USAHA RAKYAT (KUR) BAGI PENGEMBANGAN UMKM DI KOTA MEDAN (STUDI KASUS BANK BRI) - Dewi Anggraini; Syahrir Hakim Nasution (Ekonomi dan Keuangan, 2013)
ABSTRACT The objective of this research is to know The role of the People’s Business Credit (KUR) for development of UMKM in Medan (Case Study of Bank BRI). The role is measured from income earned UMKM enterpreneurs after getting help from People’s Business Credit (KUR) of Bank BRI and what is the most dominant factor that encourage UMKM enterpreneurs took the People’s Business Credit (KUR) at Bank BRI. The results showed that a significant KUR capital for revenue growth of UMKM in Medan. This can be seen by the results of the analysis of the estimation model, it can be seen that: t *> t-table (4111> 1.669013). Thus Ha is accepted, it means capital KUR significant or significant impact on earnings UMKM entrepreneurs at 95% confidence level. And the most dominant factor that encourage the UMKM entrepreneurs to take or use the  People’s Business Credit (KUR) in BRI loan interest rates lower by 37.31% followed by 29.85% recommended by a friend, easy administration of 17.91%, a longer repayment period by 7.46% and good service at 7.46%.   Keywords : People’s Business Credit (KUR), Micro, Small and Medium Enterprises (UMKM)